Sugarcane bagasse - The future composite material: A literature review - Debnath, Sujan; Rahman, Ekhlasur; Das, Cecilia; Loh, Y. (Elsevier, 2013)
The natural, bio-degradable features and chemical constituents of the sugarcane bagasse (SCB) have been attracting attention as a highly potential and versatile ingredient in composite materials. Eco-friendly and low cost considerations have set the momentum for material science researchers to identify green materials that give low pollutant indexes. Various components of SCB is shown to possess the ability of being applied as raw material for manufacturing of composite materials at multiple levels of properties and performances. Studies on the impacts, performances and applications of SCB in its original condition; transformed forms; treated with appropriate chemicals and/or processes; in combination with materials of distinct properties and manipulation of manufacturing methodologies have been duly considered. This paper attempts to summarize a review of current literature on the extensive studies that have been undertaken in an attempt to explore plausible applications and potentials of SCB for composite material.